2021
DOI: 10.1155/2021/1830790
|View full text |Cite
|
Sign up to set email alerts
|

LINC01355 Contributes to Malignant Phenotype of Oral Squamous Cell Carcinoma and Cytotoxic T Cell Infiltration via Activating Notch Signaling Pathway

Abstract: LINC01355 has been demonstrated to be dysregulated in several cancers. However, the exact molecular function of LINC01355 in the pathogenesis of OSCC remains unstudied. Here, we reported the effect of LINC01355 in OSCC and investigated the mechanisms. Firstly, we found that the results indicated LINC01355 was increased in OSCC cells. Knockdown of LINC01355 repressed OSCC cell proliferation, migration, and invasion. Recently, immunotherapy is a significant method for the treatment of cancers, in which CD8+ T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Conversely, LINC01355 inhibits the growth of breast cancer by inhibiting FOXO3-mediated CCND1 transcription [ 56 ]. Conversely, it activates the Notch signaling pathway to promote the malignant phenotype of oral squamous cells and the invasion of cytotoxic T cells [ 57 ]. Currently, many studies have found a close relationship between USP30-AS1 and autophagy in cancer [ 58 61 ], though there is no study on the relationship between USP30-AS1 and necroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, LINC01355 inhibits the growth of breast cancer by inhibiting FOXO3-mediated CCND1 transcription [ 56 ]. Conversely, it activates the Notch signaling pathway to promote the malignant phenotype of oral squamous cells and the invasion of cytotoxic T cells [ 57 ]. Currently, many studies have found a close relationship between USP30-AS1 and autophagy in cancer [ 58 61 ], though there is no study on the relationship between USP30-AS1 and necroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no relevant reports on RCC in general. LINC01355 was reported to be a tumor suppressor in breast cancer [ 59 ] and a tumor enhancer in gastric cancer [ 60 ] and oral squamous cell carcinoma [ 61 ]. The regulatory mechanisms of SNHG1 in cancers have been widely studied.…”
Section: Discussionmentioning
confidence: 99%